BDNF rescues prefrontal dysfunction elicited by pyramidal neuron-specific DTNBP1 deletion in vivo. (17th August 2016) - Zhang, Wen; Daly, Kathryn M.; Liang, Bo; Zhang, Lifeng; Li, Xuan; Li, Yun; Lin, Da-Ting
Abstract: Dystrobrevin-binding protein 1 ( Dtnbp1 ) is one of the earliest identified schizophrenia susceptibility genes. Reduced expression of DTNBP1 is commonly found in brain areas of schizophrenic patients. Dtnbp1 -null mutant mice exhibit abnormalities in behaviors and impairments in neuronal activities. However, how diminished DTNBP1 expression contributes to clinical relevant features of schizophrenia remains to be illustrated. Here, using a conditional Dtnbp1 knockout mouse line, we identified an in vivo schizophrenia-relevant function of DTNBP1 in pyramidal neurons of the medial prefrontal cortex (mPFC). We demonstrated that DTNBP1 elimination specifically in pyramidal neurons of the mPFC impaired mouse pre-pulse inhibition (PPI) behavior and reduced perisomatic GABAergic synapses. We further revealed that loss of DTNBP1 in pyramidal neurons diminished activity-dependent secretion of brain-derived neurotrophic factor (BDNF). Finally, we showed that chronic BDNF infusion in the mPFC fully rescued both GABAergic synaptic dysfunction and PPI behavioral deficit induced by DTNBP1 elimination from pyramidal neurons. Our findings highlight brain region- and cell type-specific functions of DTNBP1 in the pathogenesis of schizophrenia, and underscore BDNF restoration as a potential therapeutic strategy for schizophrenia.